Microcontroller Based Fire Alarm System Using Sensory and Monitoring System - L. Ravindran; Md Ghazaly, Mariam; Che Amran, Aliza (2007)
Fire alarm system plays an important role in maintaining and monitoring the safe of all kind environments and situations. However the usability of many existing fire alarm system is well known but could he produce with high cost. Subsequently, it is not affordable for the low income users. This paper will discuss the design and implementation of a fire alarm system using the microcontroller which is been produced with low cost and with effective outcome. The outcome of this fire alarm system is almost the same compared to the existing fire alarm system in the market which is been produced with higher cost.